Transcriptome profiling of genes differentially modulated by sulfur and chromium identifies potential targets for phytoremediation and reveals a complex S-Cr interplay on sulfate transport regulation in B. juncea - Schiavon, Michela; Wirtz, Markus; Hell, Rüdiger (Journal of hazardous materials, 2012)
A differential display cDNA-AFLP derived technique was used to identify gene transcripts regulated by chromium (Cr) in relation to sulfur (S) nutrition in Brassica juncea. Twelve-day old plants were grown with 200 μM sulfate (+S), without sulfate (−S), with 200 μM sulfate plus 200 μM chromate (+S + Cr), or without sulfate plus 200 μM chromate (−S + Cr). Forty-four combinations of degenerate primers were assayed, which allowed the detection of 346 Transcript-Derived Fragments (TDFs) differentially regulated by Cr and S at times 0, 10 min, 1 h, 24 h. Eight sulfate transporters were identified, whose transcript abundance was dependent on the levels of plant S-compounds. For some of these transporters, a tight coordinated regulation of gene expression was observed in response to Cr. The MapMan analysis revealed a differential pattern of gene expression between +S + Cr and −S + Cr plants for several other transcripts and highlighted an overlap among responses to metals, defence against pathogens and senescence, hence suggesting the existence of common mechanisms of gene regulation. Among the identified gene transcripts, those involved in S metabolism and proteolitic processes may represent potential targets of genetic engineering in efforts to increase Cr accumulation and tolerance in plant species employed in phytoremediation techniques.